The Political Identity of Ethnicity in the Local Election of Makassar City 2018 - Asfar Mutaaly Barelly; Muhammad Muhammad; Gustiana A Kambo; Abdillah Abdillah (Journal of Governance, 2021)
The emergence of ethnic politics begins with the growth of awareness that identifies them as belonging to a particular ethnic group or group. This awareness then gave rise to group solidarity and a sense of nationality. In the context of local political dynamics in Makassar City, it is inevitable that there will be a struggle for ethnic identity politics in the struggle for the throne of power. This research method uses a qualitative-exploratory approach with a phenomenological approach, namely exploring the phenomenon of ethnic identity politics in the struggle for the throne of power in Makassar City. Data analysis using Nvivo 12 Pro qualitative research tools. The results of the study show the phenomenon of ethnic identity politics in the Makassar City Election as seen in ethnic political attacks on political communication [original Makassarese] and [immigrants] during the 2018 Makassar City Election. The victory of an empty city in the 2018 Makassar mayoral election has been described as a democratic victory. for the little people and the defeat of the local political elite. This can trigger the growth and widespread practice of ethnic identity politics in the upcoming Pilkada in Makassar City. The birth of resentment from local political elites, which is reflected in the attacks of identity politics through political communication [We are 100% Makassar, while he is 100% Gorontalo] will exacerbate political and social instability in the Makassar City area. Therefore, the maturity of the local elite is needed to create local political qualities. This political maturity will have an impact on improving the quality of politics and making local political battles more productive and healthy.